A STUDY OF THE STRUCTURE OF MIXED CATIONIC NONIONIC MICELLES BY SMALL-ANGLE NEUTRON-SCATTERING SPECTROMETRY - Cummins, P; Penfold, J; Staples, E (1992)
Small-angle neutron scattering spectrometry has been used to study the geometry of mixed cationic/nonionic micelles of hexadecyltrimethylammonium bromide (C16TAB) and hexaethylene glycol monododecyl ether (C16E6). The anisotropic interacting micelles show a temperature dependence of the micelle geometry similar to that previously observed for C16E6 alone. The results demonstrate the existence of the theoretically predicted local ordering in strongly interacting anisotropic systems.